Non-quantal acetylcholine release after cholinesterase inhibition in vivo - Nikolsky, E E; Oranska, T I; Vyskocil, F (Physiological research, 1992)
After anticholinesterase treatment in vivo, depolarization of the postsynaptic muscle fibre membrane by about 4 mV develops due to non-quantally released acetylcholine from the motor nerve terminal. This conclusion was supported by experiments with the curarization of diaphragm slices from anticholinesterase treated mice during intracellular microelectrode recordings.
Keywords: Electrophysiology; Acetylcholine; Armin; acetylcholin; mužské pohlaví; elektrofyziologie; Mice; armin; ženské pohlaví; zvířata; Cholinesterases; cholinesterasy; myši; nervosvalová ploténka; Motor Endplate; soman; Female; Soman; Male; Animals